An Empirical Study on Impact of Project Management Constraints in Agile Software Development: Multigroup Analysis between Scrum and Kanban - Sathe, Chaitanya Arun; Panse, Chetan (Brazilian Journal of Operations & Production Management, 2023)
Goal: The Study aims to investigate the impact of project management constraints in fixed-cost and fixed-scheduled Agile software development contracts using multigroup analysis (MGA) to perform repeated comparisons of parameters across groups of Scrum or Kanban methodologies using structural equation modelling (SEM) Design/Methodology/Approach: A web-based survey is used to collect responses to a questionnaire based on project management constraints for Kanban and Scrum method-based Agile software development projects from people working on projects fixed-cost and fixed-schedule contracts and then analyzed with the help of multi-group analysis using SmartPLS 4.0 Results: Risk management has a mediating effect between project scope, resources, and delivery quality. MGA implied that the Kanban method is better at managing resources and will have a higher impact on the quality of deliverables than the Scrum method. Limitations of the investigation: Evaluating the suitability of various multi-group analysis approaches requires more than just our empirical example using satisfactory data and other project management constraints. Practical implications: The findings of the study suggest that hypothesis testing should be carried out for a distinct model parameter between study groups, whenever they are comparing more than two group. Originality/Value: This study helps in contributing to exploring PLS route modelling by the introduction of the original non-parametric confidence set approach based on a comparison of parameter estimations and bootstrap confidence intervals. The study investigates the impact of several project management constraints on to fixed-cost Agile software development projects.